2010
DOI: 10.1016/j.neuro.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Rho kinase inhibitor Y-27632 facilitates recovery from experimental peripheral neuropathy induced by anti-cancer drug cisplatin

Abstract: Chemotherapy drugs have neurotoxicity associated with treatment, which can become a doselimiting problem when clinical presentation is severe. However, there is no effective therapy to circumvent the neurotoxicity of anti-cancer drug treatment. In this study, we utilized a newly designed mouse model of cisplatin-induced peripheral neuropathy to determine both the severity of neurotoxicity induced by drug treatment and the effectiveness of the Rho kinase inhibitor Y-27632 in post-treatment recovery. Sensory ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…All animals were subjected to Von Frey/Semmes-Weinstein monofilament sensory threshold testing of the hind paws as previously described (James et al, 2010) every two weeks for the 10 week treatment period. Briefly, animals were placed within a clear plastic barrier upon an elevated screen and allowed to acclimate for 10 to 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All animals were subjected to Von Frey/Semmes-Weinstein monofilament sensory threshold testing of the hind paws as previously described (James et al, 2010) every two weeks for the 10 week treatment period. Briefly, animals were placed within a clear plastic barrier upon an elevated screen and allowed to acclimate for 10 to 15 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies from our laboratory have demonstrated that Rho pathway inhibition, either upstream with a p75 neurotrophin receptor (p75 NTR ) small molecule ligand (LM11A-31, Massa et al, 2006) or downstream with a selective p160 ROCK / Rho kinase inhibitor (Y-27632), facilitates neuronal recovery in neuronal cultures treated with cisplatin (James et al, 2008). Subsequent in vivo studies, using a CIPN mouse model, demonstrated that Y-27632 inhibited cisplatin-induced RhoA pathway activation and promoted recovery from peripheral neuropathy (James et al, 2010). These findings highlight the potential importance of RhoA signaling in CIPN and raise the possibility that a clinically viable way to inhibit RhoA activation might serve to inhibit neuronal toxicity and thereby enhance current cisplatin treatment paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] It has also been reported that Y-27632 has a protective effect on human embryonic stem cells, human bone marrow-derived mesenchymal stem cells, and endothelial cells. [19][20][21] It has been shown that Y-27632 has a suppressive effect on the invasion and migration of human bladder cancer TSGH cells 14 and on the adhesion and mobility of esophageal squamous cancer cells.…”
Section: Effects Of Srf-sirna(1107) and Y-27632 On The Proliferationmentioning
confidence: 98%
“…The drug has been shown beneficial in animal-model studies of autoimmune diseases such as myasthenia gravis, psoriasis, arthritis, and autoimmune encephalomyelitis [6] . Therapeutic effectiveness of anti-cancer drugs is associated with severe side effects due to their toxicity [7] . Bortezomib is one of the more widely used anti-cancer drugs for a number of cancers and is metabolized in the liver, which can develop drug toxicity due to these metabolisms [8] .…”
Section: Introductionmentioning
confidence: 99%